Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Insurance Sector. (IMF Staff Country Reports; Country Report, 2014)
This Technical Note provides an update on the Austrian insurance industry and an analysis of its regulatory and supervisory regime. The structure of the domestic insurance sector has remained largely stable since the last update. At Q3-2012 there were 50 insurance companies with assets of Euro 108 billion, making up nearly 40 percent of GDP. Although insurance portfolios are largely concentrated in high-quality bonds, they have significant exposure to European banks. Most insurance companies in Austria appear well capitalized under the Solvency I regime. The industry remains profitable though margins have come under some pressure recently.